2015
DOI: 10.1002/nbm.3434
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging in abdominal organs

Abstract: Initially, diffusion tensor imaging (DTI) was mainly applied in studies of the human brain to analyse white matter tracts. As DTI is outstanding for the analysis of tissue´s microstructure, the interest in DTI for the assessment of abdominal tissues has increased continuously in recent years. Tissue characteristics of abdominal organs differ substantially from those of the human brain. Further peculiarities such as respiratory motion and heterogenic tissue composition lead to difficult conditions that have to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 135 publications
(204 reference statements)
0
13
0
Order By: Relevance
“…Taouli et al showed that diffusion is isotropic in the liver parenchyma ( 20 ), whereas Tosun et al observed a significant nonzero value for fractional anisotropy (FA) in the liver (average FA, 0.48) using diffusion tensor imaging (DTI) measurements, indicative of substantial anisotropy in the liver parenchyma ( 21 ). Kidney diffusion anisotropy has been studied quite extensively with DTI, showing significant anisotropy, particularly in the renal medulla (FA range: 0.24–0.57 in the medulla compared with 0.13–0.31 in the cortex) ( 22 ). Diffusion in the pancreas has also been shown to be anisotropic (mean FA, 0.38) ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taouli et al showed that diffusion is isotropic in the liver parenchyma ( 20 ), whereas Tosun et al observed a significant nonzero value for fractional anisotropy (FA) in the liver (average FA, 0.48) using diffusion tensor imaging (DTI) measurements, indicative of substantial anisotropy in the liver parenchyma ( 21 ). Kidney diffusion anisotropy has been studied quite extensively with DTI, showing significant anisotropy, particularly in the renal medulla (FA range: 0.24–0.57 in the medulla compared with 0.13–0.31 in the cortex) ( 22 ). Diffusion in the pancreas has also been shown to be anisotropic (mean FA, 0.38) ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, simple DWI experiments using two b ‐values assume monoexponential SI decay and yield an averaged ADC over three orthogonal directions, disregarding the non‐monoexponential contribution of the fast “pseudo‐diffusion” component, caused by microperfusion, as well as directional dependency (anisotropy) of the diffusion processes in the structured tissue. In recent years technical advances have improved the acquisition of abdominal DW images in terms of quality and speed, allowing the investigation of advanced diffusion MRI modeling in abdominal studies, including in the pancreas. These advanced approaches consist of further sampling and analysis frameworks that capitalize on tissue qualities such as microstructural anisotropy and microvascularity, in the form of diffusion tensor imaging (DTI), which extends the spatial information acquired, and the intravoxel incoherent motion (IVIM) model, which extends the number of diffusion weightings, allowing compartmental separation.…”
Section: Diffusion Mri Of the Pancreasmentioning
confidence: 99%
“…Mainly used in neuroimaging studies for the characterization of brain white matter tracts 6 , DTI has been recently applied to different intra-abdominal organs 7 including prostate 810 , liver 11,12 and kidney 13,14 . DTI is particularly suitable for kidney studies due to well-defined structural organization.…”
Section: Introductionmentioning
confidence: 99%